Is the Illegal Trade of Glass Eels (Anguilla anguilla) Increasing the Spread of Disease? A Case of EVEX - Ivana Giovanna Zupičić; Dražen Oraić; Željko Pavlinec; Dinko Novosel; Luka Žuvić; Tanja Šegvić-Bubić; Snježana Zrnčić (Microorganisms, 2022)
The European eel (Anguilla anguilla) is a catadromous species that inhabits the rivers of the Adriatic watershed in Croatia. It is a critically endangered fish species, according to the IUCN, due to its declining abundance in European rivers caused by overfishing and trafficking and by diseases caused by nematodes, pathogenic bacteria and viruses. An illegal parcel of glass eels was confiscated at the Zagreb Airport and was intended to re-populate Croatian rivers. Barcoding was employed to determine species affiliation, and a thorough health check was carried out. This study reports the evaluation of gross lesions, histological findings, and EVEX virus isolation and identification. Since the confiscated glass eels were of unknown origin and given the serological and genetic similarities of EVA and EVEX, we designed primers and probes for almost whole genome sequencing to elucidate the origin of glass eels based on viral phylogeny. Bayesian phylogeny showed that the isolated strain had the most common ancestor with a Danish isolate and likely evolved from the French isolate of EVEX. These findings are discussed in light of the divergence of recently isolated strains and their possible contribution to the decrease of the abundance of the European eel in European waters.